Pull Off test to evaluate the compressive strength of concrete: an alternative to Brazilian standard techniques - E. Pereira; M. H. F. de Medeiros (Revista IBRACON de Estruturas e Materiais)
To estimate the compressive strength of concrete is necessary in many reinforced concrete structures inspection works. In Brazil, the standard tests for this purpose are: Compressive test in drilled cores, rebound hammer test and ultrasonic test. In the United States and Europe are also regulated other techniques. The aim of this paper is to analyze the use of Pull Off test as an inspection tool of concrete and also disclose the possibility of use of complementary techniques to the standard ones in Brazil. The results show that the Pull Off test results in high correlation (R²> 0.93) with the compressive strength, measured in cylindrical and prismatic specimens. The rebound hammer test did not show satisfactory correlation (R²≅0.6) for the case of cylindrical specimens. The ultrasonic test showed high correlation (R²> 0.98), but behaves differently with the shape changing of the specimens.